Evaluating the contribution of oocyte, sperm, and uterus in determining the outcome of intracytoplasmic sperm injection - A retrospective observational comparative study on intracytoplasmic sperm injection using own oocytes and donor oocytes - Deepeka Thangamani Shanthi; Parasuram Gopinath; Karthika D Kumar; Ramesh Parameswara Iyer; Revathi Kesavaramanujam; Gopinathan Kannoly Karunakaran (Wolters Kluwer Medknow Publications, 2021)
Context: Several studies have assessed the contribution of oocyte, sperm, and endometrium on the outcome of intracytoplasmic sperm injection (ICSI) separately. This study assesses the relative contribution of oocyte, sperm, and uterus in achieving clinical pregnancy (CP) through ICSI by comparing own and third-party ICSI cycles. Aim: The aim of the study is to evaluate and compare the strength of contribution of oocyte, sperm, and uterus in achieving CP through ICSI. Settings and Design: This retrospective observational study of ICSI cycles for 20 months including 1000 embryo transfers (ETs). Methodology: Subjects were divided into two groups, Group 1 - ICSI with own oocytes (550 ETs) and Group 2 - ICSI with donor oocytes (450 ETs). Both the groups had 3 subgroups - a (husband sperm, transferred to self), b (donor sperm, transferred to self), c (husband sperm, transferred to a gestational surrogate). CP rate (CPR) as a major outcome was studied in the groups and subgroups. Statistical Analysis: CPR was compared between various subgroups using Z-test and Chi-square of significance of difference between proportions. A P < 0.05 was taken as the level of statistical significance. Results: CPR in subgroup 1a < 35 years, 1a ≥35 years, and 2a was 42.98%, 26.21%, and 40.92%, respectively (P = 0.001). CPR was compared between 2a and 2c (40.92%, 56.5%, P = 0.044) and between 2a and 2b (40.92%, 42.11%, P = 0.866). Implantation rate was highest in Group 2c (34.88%) compared to other subgroups. Conclusion: The higher CPR in women <35 years undergoing ICSI with own oocytes than older women and a comparable CPR as that of recipients of donor oocytes suggests that age thereby oocyte quality is the strongest determining factor in achieving clinical pregnancy. Among oocyte recipients, higher CPR in surrogate uterus than patient uterus suggests that uterus/endometrium plays a considerable role, and comparable CPR between ICSI using husband sperm and donor sperm indicates that sperm quality might not play a major role in achieving CP.